Ascorbate induces apoptosis in melanoma cells by suppressing Clusterin expression - Sushmita Mustafi (Nature Portfolio, 2017)
Abstract Pharmacological levels of ascorbate have long been suggested as a potential treatment of cancer. However, we observed that EC50 of ascorbate was at a similar level for cultured healthy melanocytes and melanoma cells, suggesting a limit of pharmacological ascorbate in treating cancer. Loss of 5-hydroxymethylcytosine (5 hmC) is an epigenetic hallmark of cancer and ascorbate promotes 5 hmC generation by serving as a cofactor for TET methylcytosine dioxygenases. Our previous work demonstrated that ascorbate treatment at physiological level (100 μM) increased 5 hmC content in melanoma cells toward the level of healthy melanocytes. Here we show that 100 µM of ascorbate induced apoptosis in A2058 melanoma cells. RNA-seq analysis revealed that expression of the Clusterin (CLU) gene, which is related to apoptosis, was downregulated by ascorbate. The suppression of CLU was verified at transcript level in different melanoma cell lines, and at protein level in A2058 cells. The anti-apoptotic cytoplasmic CLU was decreased, while the pro-apoptotic nuclear CLU was largely maintained, after ascorbate treatment. These changes in CLU subcellular localization were also associated with Bax and caspases activation, Bcl-xL sequestration, and cytochrome c release. Taken together, this study establishes an impending therapeutic role of physiological ascorbate to potentiate apoptosis in melanoma.